4′-Chlorodiazepam modulates the development of primary hippocampal neurons in a sex-dependent manner. (3rd February 2017) - Arbo, B.D.; Vieira-Marques, C.; Ruiz-Palmero, I.; Ortiz-Rodriguez, A.; Arevalo, M.A.; Garcia-Segura, L.M.; Ribeiro, M.F.
Highlights: TSPO ligands have been used as neurotherapeutic agents in different models. TSPO ligands effects on neuronal development are not known. 4′-CD developmental effects in male and female hippocampal neurons were evaluated. There were sex-differences in the development of male and female hippocampal neurons. 4′-CD stimulated the development of male, but not from female hippocampal neurons. Abstract: The translocator protein 18 kDa (TSPO) is located in the outer mitochondrial membrane and is involved in the cholesterol transport into the mitochondria and in the regulation of steroidogenesis and other mitochondrial functions. It is known that steroid hormones, such as estradiol, testosterone and dihydrotestosterone are neuroprotective and regulate neuritogenesis in the CNS by different mechanisms. However, the developmental effects of TSPO ligands in the CNS are not known. Therefore, the aim of this study was to identify the developmental effects of 4′-chlorodiazepam (4′-CD), a TSPO ligand, in primary cultures of male and female mouse hippocampal neurons. We observed that female neurons showed an advanced neuritogenesis compared to male neurons after 2 days in vitro . Moreover, it was shown that 4′-CD administration accelerated the maturation of male hippocampal neurons, without changing the development of female neurons. These findings, showing that 4′-CD modulates the development of hippocampal neurons in a sex-dependent manner, suggest that TSPO may be involved in the regulation of neuritogenesis.